Expression of intermediate filament nestin in blood vessels of neural and non-neural tissues - Mokrý, Jaroslav; Ehrmann, Jirí; Karbanová, Jana; Cízková, Dana; Soukup, Tomás; Suchánek, Jakub; Filip, Stanislav; Kolár, Zdenĕk (Acta medica (Hradec Kralove), 2008)
Our previous findings performed in rat tissues demonstrated that intermediate filament nestin is expressed in endothelial cells of newly formed blood vessels of developing organs and neural transplants. The aim of the present study was to identify other cellular markers expressed in nestin-positive (nestin+) blood vessels. To reach this goal we performed double immunofluorescent study to co-localize nestin with endothelium-specific markers (CD31, CD34 II, vimentin) or markers of perivascular cells (GFAP, SMA) in paraffin-embedded sections of normal human brain tissue, low- and high-grade gliomas, postinfarcted heart and samples of non-neural tumours. Our findings documented that all the samples examined contained blood vessels with different ratio of nestin+ endothelial cells. Double immunostaining provided unambiguous evidence that endothelial cells expressed nestin and allowed them to distinguish from other nestin+ elements (perivascular astrocytic endfeet, undifferentiated tumour cells, smooth muscle cells and pericytes). Nestin+ endothelium was not confined only to newly formed capillaries but was also observed in blood vessels of larger calibres, frequently in arterioles and venules. We conclude that nestin represents a reliable vascular marker that is expressed in endothelial cells. Elevation of nestin expression likely corresponds to reorganization of intermediate filament network in the cytoskeleton of endothelial cells in the course of their maturation or adaptation to changes in growing tissues.
Keywords: Brain Neoplasms; Actins; Endothelium, Vascular; imunohistochemie; antigeny CD31; aktiny; Glial Fibrillary Acidic Protein; Nestin; mozek; Antigens, CD34; Nerve Tissue Proteins; Blood Vessels; Neoplasms; cévy; Immunohistochemistry; Brain; Coronary Vessels; Humans; nádory; vimentin; Intermediate Filament Proteins; proteiny nervové tkáně; nádory mozku; Platelet Endothelial Cell Adhesion Molecule-1; cévní endotel; gliový fibrilární kyselý protein; antigeny CD34; proteiny intermediálních filament; nestin; Vimentin; koronární cévy; lidé